Real Effects of Financial Reporting on Innovation: Evidence from Tax Law and Accounting Standards - Williams, Braden; Williams, Brian M (The Accounting Review, 2021)
ABSTRACT This study examines whether financial accounting standards moderate the effectiveness of tax policy. Specifically, we examine whether myopic managers' focus on short-term financial reporting reduces the effectiveness of tax subsidies that incentivize innovation. We employ a novel setting, the issuance of Financial Interpretation No. 48 (FIN 48), which changed the financial reporting for some important, yet uncertain, tax incentives to innovate. For firms most affected by the standard change, we find evidence of reduced investment in innovation, reduced sensitivity of investment to tax incentives, and reduced future innovative output. Consistent with earnings myopia, we find the effect is more pronounced in firms with higher levels of transient institutional ownership and newly vesting equity compensation. These results indicate financial reporting myopia has real effects on innovation and can reduce tax policy effectiveness. The results further suggest that tax policymakers should consider both financial reporting and cash flow incentives in designing policy.